STRATEGI PENGELOLAAN WAKAF PRODUKTIF NAHDLATUL ULAMA DI PCNU GUNUNGKIDUL YOGYAKARTA - Nurhidayatuloh, Nurhidayatuloh (Jurnal Ekonomi Bisnis Kompetif, 2025)
The problem formulation of this research is how to manage productive waqf in the Nahdlatul Ulama (PCNU) Gunungkidul Branch Management and the aim of this research is to find out the productive waqf management strategy implemented in PCNU Gunungkidul. This research uses a qualitative research approach and a field study type of research. The data sources listed are based on the results of interviews, observations and documentation with the chairman of PCNU Gunungkidul, PCNU Gunungkidul waqf administrators, chairman of MWCNU Karangmojo, administrators of the Miftahul Falah Islamic boarding school. The results of this research indicated that: the productive waqf management mechanism at PCNU Gunungkidul starts from MWCNU, which also acts as a trustee who consistently engages in consultations and agreements when dealing with or managing the waqf. They then maximize the potential of the waqf assets, thereby enhancing the economic and social well-being of the community. The strategies for productive waqf management at PCNU Gunungkidul include the allocation of waqf by MWCNU, such as providing land for agricultural purposes, which is subsequently handed over to the designated managers. This is followed by planning, execution, and supervision stages for the existing waqf, progressing to evaluation and environmental assessment. An example of productive waqf in the Karangmojo district is the Miftahul Falah Islamic boarding school with the agricultural land is utilized for cultivation, then the harvest is sold, and the profits from the sales are used for future development at the Islamic boarding school